KEBIJAKAN PROTEKSIONISME AMERIKA SERIKAT TERHADAP REPUBLIK RAKYAT CINA - Ernawati Batubara; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Abstract U.S. and China have had trade cooperation since a few decades ago. U.S. thought that China could be a pusher for the economic of its country. The first step was given to China  entering WTO. So, every barriers from international trade could minimize. But, China and world were taken aback that U.S. apply protectionism policy. That is different from the beginning commitment from U.S.. This research examines about the protectionism policy which United States does to China protecting trade goods U.S.. The method that used in this research is qualitative. All of the data are by library research. China is the biggest partner of U.S in international trade. But, the rising of China’s economic with China’s defeitculnesses that had been found from Section 301 investigation making the U.S position in hegemonic economy in the world be starting shif. That is why U.S wants to protect their position and rights that has been stolen by China. The protectionism appears as a result from Section 301 that give U.S Presiden making new tariffs about impor tariffs from China. The goal of the protectionism is to make renegoitation about structural trade between both countries. This goal is the main reason caused of protectionism policy.  Protectionism isn’t the end of their trade but the beginning for new agreement reached.Keywords: Protectionism, tariff, section 301, deficit, export, import, intellectual proverty, hegemony, jobs